An Ayurvedic Drug Review of Yashtimadhu (Glycyrrhiza glabra L.) - Menon, Sudeep; Lavagale, Pooja; Maru, Shyam; Bari, Kashinath; Dasmohapatra, Ashutosh (Journal of Neonatal Surgery, 2025)
Yashtimadhu, scientifically known as Glycyrrhiza glabra L., is a revered herb in Ayurveda, recognized for its diverse therapeutic properties. This paper presents a comprehensive review of Yashtimadhu, exploring its classical Ayurvedic attributes, chemical composition, pharmacological actions, traditional uses, clinical applications, and safety considerations. Through a synthesis of traditional Ayurvedic knowledge and contemporary scientific research, this review aims to provide a holistic understanding of Yashtimadhu's potential as a valuable medicinal agent.